Bayesian classifier for multi-oriented video text recognition system. Issue 13 (1st August 2015) - Roy, Sangheeta; Shivakumara, Palaiahnakote; Roy, Partha Pratim; Pal, Umapada; Tan, Chew Lim; Lu, Tong
Highlights A new system for recognizing text in video through binarization. Exploring wavelet and gradient sub-bands for enhancing text information. Introducing Bayesian classifier in novel way for binarization. Use of connected component analysis for restoring missing information. Experimental results on both video and scene text shows the method is superior.